Literary non-fiction and the unstable fault line of the imaginative and the reportorial : Antjie Krog’s, Country of my skull, Pumla Gobodo-Madikizela’s, A human being died that night and Sindiwe Magona’s, Mother to mother - Fransman, Jolene (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.